2017
DOI: 10.1186/s12891-017-1622-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of failed reimplantation arthroplasty for periprosthetic hip infection

Abstract: BackgroundTwo-stage reimplantation arthroplasty is one of the standard treatments for chronic periprosthetic joint infection (PJI). Scanty data exist regarding the risk factors for failure after two-stage reimplantation for periprosthetic hip infection. The purpose of this study was to investigate and identify the risk factors associated with failure after two-stage reimplantation hip arthroplasty.MethodsSixty-two patients with hip PJI treated with a two-stage reimplantation protocol at our institution from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…Recurrence and repetitive infections may cause troublesome complications such as bone loss, poor soft tissue integrity, prolonged and complex operations, and physical and psychological disabilities. Because of the change in character of the remaining bone, the shear strength at the bone-cement interface is reduced and the cement-microinterlock necessary for long-term stability is lost [14,15]. In particular, in the setting of infection, when acetabular bone loss is severe, the challenge for surgeons can be even greater due to the difficulty in implanting a stable cement spacer while keeping in mind the need for future surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence and repetitive infections may cause troublesome complications such as bone loss, poor soft tissue integrity, prolonged and complex operations, and physical and psychological disabilities. Because of the change in character of the remaining bone, the shear strength at the bone-cement interface is reduced and the cement-microinterlock necessary for long-term stability is lost [14,15]. In particular, in the setting of infection, when acetabular bone loss is severe, the challenge for surgeons can be even greater due to the difficulty in implanting a stable cement spacer while keeping in mind the need for future surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed sonication of antibiotic spacers could disrupted biofilm and led to higher rates of positive intraoperative cultures [38, 39]. Kheir et al reported that positive leukocyte esterase (LE) strip test might be used in diagnosing persistent infection and resulted in a higher rate of subsequent failure [26]. Recently, Shahi et al reported D-dimer might be useful in diagnosing infection before reimplantation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the current literature of single-stage revision surgery with eradication-rates of 70% to over 90% and two-stage revision surgery with eradication-rates of 80% up to over 90% our results are comparable. 7,[16][17][18][19][27][28][29][30][31][32][33][34] The reason for the high infection control might be due to the young age with less comorbidity of the cohort group and an intact immune system of patients selected for this study. We herewith provide the first data in young patients undergoing single-stage septic revision in patients with PJI in THA, justifying this approach.…”
Section: Discussionmentioning
confidence: 99%